Study protocol: Hypersexual and hyposexual behavior among adults diagnosed with alcohol- and substance use disorders—Associations between traumatic experiences and problematic sexual behavior - Jepsen, Dennis; Luck, Tobias; Bernard, Marie; Moor, Irene; Watzke, Stefan (Frontiers in Psychiatry, 2023)
Background. Hypersexual and hyposexual behaviors are common concomitant of substance use disorders (SUD). On the one hand, the regular consumption of alcohol or illegal drugs can lead to hypersexual or hyposexual behavior due to its effects on the organism; on the other hand, the use of psychotropic substances is also used as a coping strategy concerning already existing sexual impairments. The aforementioned disorders show similarities in terms of their etiology, as traumatic experiences get special attention as potential risk factors for the development of addictions, hypersexual, and hyposexual behavior. Objectives. The study aims to explore the association between SUD characteristics and hypersexual/ hyposexual behavior, and a potential moderating effect of early traumatic life events by answering the following research questions: 1) Do people with SUD differ from a sample of people with other psychiatric disorders regarding hypersexual and hyposexual behavior? 2) What are the associations between the presence of sexual problems and different characteristics of the SUD (e.g., mono vs. polysubstance use, type of addictive substance, intensity of the disorder)? 3) What influence do traumatic experiences in childhood and adolescence have on the existence of sexual disorders among adults with a diagnosed SUD? Method. The target group of this cross-sectional ex-post-facto study comprises adults diagnosed with an alcohol- and/ or substance use disorder. Data will be collected with an online survey, which will be promoted via several support and networking services for people diagnosed with SUD. Two control groups will be surveyed, one consisting of people with other psychiatric disorders than SUD and traumatic experiences, and one healthy group. Relations between the dependent variables (hypersexual and hyposexual behavior) and independent variables (sociodemographic information, medical and psychiatric status, intensity of the prevalent SUD, traumatic experiences, and symptoms of posttraumatic stress disorder) will be initially calculated via correlations and linear regression. Risk factors will be identified via multivariate regression. Discussion. Gaining relevant knowledge promises new perspectives for prevention, diagnosis, case conception, and therapy of SUDs as well as problematic sexual. The results can provide more information about the importance of psychosexual impairments regarding the development and maintenance of SUDs.